The The Utilization of Using Youtube Videos to Improve Students Speaking Skills During Online Learning at Ban Kaengsriphoom School, Thailand: English - Yunita Aliffia; Yudhi Arifani (Journal of English Development, 2024)
This study aims to analyze the utilization of using YouTube video media to improve the English speaking ability of Grade 6 students at Ban Kaengsriphoom school, Thailand. The method used in this study is mixed method research with explanatory design type. The researcher collected quantitative data by distributing questionnaires to 20 students first and then implemented qualitative data by conducting interviews with 3 students to add more in-depth results. Researchers analyzed the data obtained from the questionnaire analyzed using Likert scale calculations with the frequency of answers given by students expressed in percentage form and then conducted interviews. From the results of quantitative and qualitative analysis, it is known that most students feel happy using YouTube media in learning English. YouTube videos can improve students' speaking skills. Furthermore, students gave positive responses during data collection. Choosing interesting learning media can facilitate students in learning and increase student motivation because YouTube presents a combination of images, animations, text, and sound making students enthusiastic in learning English, especially in speaking skills.